Aplicación de estrategias pedagógicas para el desarrollo del aprendizaje significativo de la asignatura de programación en los estudiantes del bachillerato de la especialidad de informática del colegio fiscal mixto Dr Camilo Gallegos Domínguez del cantón Arenillas periodo lectivo 2013-2014. - Fáres Chérrez, Adriana Mónica (2014)
Develop meaningful learning in students within the research process were applied hypothetical, deductive and inductive methods for the approach and analysis of the information at the end of the research, we conclude that the suso of active methodologies through the technology.